Molecular biomarkers in idiopathic pulmonary fibrosis and disease severity - Crestani, B. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Despite major accomplishments in our understanding of idiopathic pulmonary fibrosis (IPF), its diagnosis, and management continues to pose significant challenges. The clinical management of IPF remains a major challenge due to a limited number of effective drug therapies, as well as accurate indicators of disease progression. Most patients die within at least five years after diagnosis. The identification of more accurate predictors of prognosis and survival in IPF is critical for physicians and would be useful to facilitate counselling of patients and their families, to aid communication among providers, and to guide optimal timing of transplantation. Improvements in molecular techniques have developed our understanding of IPF and have led to the identification of new pathways and a more targeted approach to the treatment of IPF with potentially novel anti-fibrotic agents. These insights have led to an increased interest in biomarkers of IPF disease progression. Although there are no validated biomarkers that are currently available, the need for surrogates of diagnosis, prognosis, and monitoring of disease course is great. However, there is currently no established method of combining these predictors to accurately determine prognosis or define disease stage.